2015
DOI: 10.1007/s10620-015-3564-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Insulin Resistance in Subjects with Nonalcoholic Fatty Liver Disease and Its Predictors in a Chinese Population

Abstract: Chinese NAFLD patients are susceptible to IR. Female sex, general and abdominal obesity, and hypertension were independent predictors for IR in NAFLD patients. FPI is an optimal predictor for IR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 40 publications
1
14
1
Order By: Relevance
“…[13] Furthermore, Li et al found female, general and abdominal obesity, and hypertension were independent predictors for IR in NAFLD patients. [14] Dixon's study showed insulin resistance and systemic hypertension, features of the metabolic syndrome, are independently associated with advanced forms of NAFLD. [15]…”
Section: Discussionmentioning
confidence: 99%
“…[13] Furthermore, Li et al found female, general and abdominal obesity, and hypertension were independent predictors for IR in NAFLD patients. [14] Dixon's study showed insulin resistance and systemic hypertension, features of the metabolic syndrome, are independently associated with advanced forms of NAFLD. [15]…”
Section: Discussionmentioning
confidence: 99%
“…The homeostasis model of assessment for insulin resistance (HOMA-IR) was calculated as [fasting plasma glucose level (mmol/l) × fasting plasma insulin level (μU/ml)]/22.5. 21 After the initial visit, the above anthropometric indexes and biochemical indicators were measured at 1, 3 and 6 months with a maximum delay of 1 month at each arranged visit.…”
Section: Methodsmentioning
confidence: 99%
“…Impaired suppression of hepatic glucose production is associated with increased intrahepatic triglyceride accumulation, which is a hallmark of NAFLD [44,45]. Most patients with type 2 diabetes experience NAFLD, and NAFLD patients have a higher risk of insulin resistance compared to healthy controls [46,47]. It is suggested that intrahepatic triglyceride content is a strong predictor of insulin action in the liver, skeletal muscle, and adipose tissues [44,45].…”
Section: Discussionmentioning
confidence: 99%